Rancang Bangun Sistem Informasi Pelacakan Dan Pemantauan Paket Kiriman Berbasis Web Dengan Bantuan Mobile Android - Indrakarna, Putu Agus Yudisuda; Sutanto, Teguh; Taufik, Vicky M. (Jurnal JSIKA, 2012)
Growing number of shipping companies is very beneficial to consumers, but not for the company. Companies should strive to improve services and to evaluate the system that had been done to be able to compete with similar companies are also doing the same thing. Companies have to lower the costs incurred during the process of delivery that has not been able to control yet. Based on these constraints, the use of geographic information systems can be used to resolve problems that occur so that companies can do the tracking and monitoring of the delivery process to improve effectiveness and efficiency of processes for cost reduction that comes out in the implementation process. Geographic information system created will provide good benefits for the customer and the company itself.   Keyword: package, gps , tracking, controling, gis